Microalgae Biotechnology - Posten, Clemens; Feng Chen, Steven (Advances in Biochemical Engineering/Biotechnology, 2016)
Antenna Mutants, Domestication, by Roberto Bassi Heterotrophic Cultivation, by William McCaffrey Chlorella for industrial applications: Advances and prospective, by Feng Chen Carotinoide, by Carola Griehl Engineering the algal chloroplast for synthesis of therapeutic proteins, by Saul Purton Design Concepts and recent developments of photobioreactors, by Clemens Posten Efficiency of flat plate reactors, by Mario Tredici Measuring modelling and control, by Olivier Bernard Microalgae in Life Support Systems, by Klaus Slenzka Heterotrophic oil production, by Makato Watanabe.